THE ROLE OF CORPORATE MANAGEMENT AND DIGITAL ECONOMY IN UZBEKISTAN - Ikromjon Musaxonzoda (Web of Journals Publishing, 2024)
This study examines the role of corporate management in supporting the digital transformation of Uzbekistan’s economy. Through an analysis of financial efficiency, productivity, risk management, and workforce development, the paper highlights the essential practices that enable Uzbek organizations to align digital strategies with corporate objectives. The findings indicate that digital tools in accounting and operational management have improved efficiency and transparency, attracting potential investments and positioning Uzbek firms competitively in the global market. Furthermore, robust corporate governance frameworks have strengthened risk management, while workforce development initiatives have addressed the digital skills gap. Despite these advancements, the study identifies challenges related to infrastructure, regulatory compliance, and the need for continuous upskilling. The results underscore that corporate management is crucial for the sustainable and effective digitalization of Uzbekistan’s economy.
Keywords: Digital economy, corporate management, Uzbekistan, financial efficiency, productivity, risk management, workforce development, digital transformation.